2021
DOI: 10.1177/1358863x21994672
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Wells score in predicting deep vein thrombosis in medical and surgical hospitalized patients with or without thromboprophylaxis: The R-WITT study

Abstract: The Wells score had shown weak performance to determine pre-test probability of deep vein thrombosis (DVT) for inpatients. So, we evaluated the impact of thromboprophylaxis on the utility of the Wells score for risk stratification of inpatients with suspected DVT. This bicentric cross-sectional study from February 1, 2018 to January 31, 2019 included consecutive medical and surgical inpatients who underwent lower limb ultrasound study for suspected DVT. Wells score clinical predictors were assessed by both ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Wells score is one of the best-known and most commonly used scoring systems in diagnosing DVT and pulmonary embolism. 12,13 According to the results of this study, the incidence of DVT in patients with a Wells score of 2 and below (low probability) was significantly lower than in those with a Wells score above two (21.8% vs. 47.1%). It is an expected result that the likelihood of DVT decreases as the Wells score drops, and it is compatible with previous studies on this subject.…”
Section: Discussionmentioning
confidence: 65%
“…Wells score is one of the best-known and most commonly used scoring systems in diagnosing DVT and pulmonary embolism. 12,13 According to the results of this study, the incidence of DVT in patients with a Wells score of 2 and below (low probability) was significantly lower than in those with a Wells score above two (21.8% vs. 47.1%). It is an expected result that the likelihood of DVT decreases as the Wells score drops, and it is compatible with previous studies on this subject.…”
Section: Discussionmentioning
confidence: 65%
“…When Söhne M, in a retrospective study, investigated the sensitivity, the negative predictive value of a non-high clinical probability of PE (based on Wells score), and a normal D-dimer result in outpatients and inpatients with suspected PE, they found that these tests were less reliable in inpatients compared to outpatients, especially in the elderly [32]. Also, the reliability of the scores for the discrimination of the risk for VTE in hospitalised patients differed among patients with or without anticoagulation treatment [33]. Furthermore, regarding the Geneva score and its revised form (revised Geneva score), it is known that both scores have been validated only in outpatients [8].…”
Section: Discussionmentioning
confidence: 99%
“…unnecessary imaging, and reduce the risk of complications. Until now, pretest probability tests such as Well's score 22 and Geneva 23 based on clinical and vital signs have been validated in several studies and showed high negative predictive values but low positive predictive values 24 , moderate accuracy and a high dependence on the population studied 25 . iv) Personalized anticoagulant management: ML-CPMs can be used to predict the response to different anticoagulant therapies or identify a personalized dosage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Until now, pretest probability tests such as Wells score 22 and Geneva 23 based on clinical and vital signs have been validated in several studies and showed high negative predictive values but low positive predictive values, 24 moderate accuracy, and a high dependence on the population studied. 25…”
Section: Applications Of ML In Vte Using Data From Ehrsmentioning
confidence: 99%
See 1 more Smart Citation